Breaching Flowery Borders: Early Twentieth Century Girls Scrapbooking Their Lives. Issue 3 (1st December 2021) - DeBauche, Leslie Midkiff
Abstract : The American high school seniors I discuss in this article graduated between 1915 and 1922, tumultuous years that included World War I, the influenza pandemic of 1918 to 1919, and the ratification of the Nineteenth Amendment. During such extraordinary times, these girls did a most ordinary thing; they made scrapbooks to commemorate their high school years.